Chemical process safety learning from case histories - Sanders, R. E. (Roy E.) (Amsterdam ; Boston : Elsevier Butterworth Heinemann, 2005)
Gives insight into eliminating specific classes of hazards, while providing real case histories with valuable messages. There are practical sections on mechanical integrity, management of change, and incident investigation programs, along with a long list of helpful resources. New chapter in this edition covers accidents involving compressors, hoses and pumps. * Stay up to date on all the latest OSHA requirements, including the OSHA required Management of Change, Mechanical Integrity and Incident Investigation regulations. * Learn how to eliminate hazards in the design, operation and maintenance of chemical process plants & petroleum refineries. * World-renowned expert in process safety, Roy Sanders, shows you how to reduce risks in your plant. * Learn from the mistakes of others, so that your plant doesn't suffer the same fate. * Save lives, reduce loss, by following the principles outlined in this must-have text for process safety. There is no other book like it!
Perspective, perspective, perspective -- Good intentions -- Focusing on water and steam: the ever-present and sometimes evil twins -- Preparation for maintenance -- Maintenance-induced accidents and process piping problems -- One-minute modifications: small quick changes in a plant can create bad memories -- Accidents involving compressors, hoses, and pumps -- Failure to use, consult, or understand specifications -- "Imagine if" modifications and practical problem solving -- The role of mechanical integrity in chemical process safety -- Effectively managing change within the chemical industry -- Investigating and sharing near misses and unfortunate incidents -- Sources of helpful information for chemical process safety.
Includes bibliographical references and index.
Keywords: Chemical processes -- Safety measures; Electronic books